2021
DOI: 10.1177/00915521211047674
|View full text |Cite
|
Sign up to set email alerts
|

“There’s So Much That We’re Doing”: How Florida College System Institutions Address Basic Needs Insecurity Among Students

Abstract: Research Question: A sizable portion of college students experience food and housing insecurity, which poses a roadblock to fully and successfully engaging in higher education. In light of these complex challenges, we ask: How do Florida College System (FCS) institutions meet the basic needs of their students? Methods: To answer the question at hand, we conducted an embedded single case study of the FCS. Between 2014 and 2019, researchers traveled to 21 Florida colleges on one or more occasions to speak with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Cross-campus collaborations to establish a "single point of contact" resource center for students can ensure that students are better supported with wraparound services (Broton, 2021;Crutchfield et al, 2020;Nix et al, 2021). Many students have difficulty locating campus support services, are unsure if they are eligible for services, and are hesitant to ask for help when needed (Umaña et al, 2022).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Cross-campus collaborations to establish a "single point of contact" resource center for students can ensure that students are better supported with wraparound services (Broton, 2021;Crutchfield et al, 2020;Nix et al, 2021). Many students have difficulty locating campus support services, are unsure if they are eligible for services, and are hesitant to ask for help when needed (Umaña et al, 2022).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The results suggest that targeted outreach efforts to specific groups of adult undergraduates (e.g., those who formerly lived in the foster care system, first-generation students) may be beneficial to those who experience higher odds of food and housing insecurity. A "single-point-of-contact" resource center that features wraparound services may reduce burdens for adult undergraduates, who may need to navigate different offices and resources (Broton, 2021;Crutchfield et al, 2020;Nix et al, 2021). Additionally, institutions can set their on-campus housing or meal plan costs on a sliding scale based upon undergraduates' income, help undergraduates locate affordable housing and daycare, and implement programs such as Swipe Out Hunger (2022), where extra unused meal plans can be donated to dining plan cards and provide free meals for students (Soria, Kelling et al, 2022).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Responsibility for children's education is a shared responsibility between the school, the community and most importantly the family. A study found that one way to maximize student learning and success is to often involve the basic needs of students and their families [23]. This involvement has a positive influence on children's development.…”
Section: Social Competencementioning
confidence: 99%